Using conversation analysis for business and management students - Greatbatch, David, 1953-; Clark, Timothy, 1964- (London : SAGE Publications Ltd, 2018)
Part of SAGE's Mastering Business Research Methods Series, conceived and edited by Bill Lee, Mark N. K. Saunders and Vadake K. Narayanan and designed to support researchers by providing in-depth and practical guidance on using a chosen method of data collection or analysis. In Using Conversation Analysis, David Greatbatch and Timothy Clark introduce the key elements of conversation analysis, an increasingly prominent form of business research analysis, which involves analysing audio and visual recordings of naturally occurring talk-in-interaction such as television speeches and interview exchanges, to see how meanings are constructed. Ideal for Business and Management students reading for a Master's degree, each book in the series may also serve as reference books for doctoral students and faculty members interested in the method. Watch the editors introduce the Mastering Business Research Methods series and tell you more about the first three books.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Conversation analysis; Nonverbal communication